Mortality and cancer incidence among female Australian firefighters. Issue 4 (23rd January 2019) - Glass, Deborah Catherine; Del Monaco, Anthony; Pircher, Sabine; Vander Hoorn, Stephen; Sim, Malcolm Ross
Abstract : Objectives: To investigate the mortality and cancer incidence of female firefighters, a group where there are limited published findings. Methods: Participating fire agencies supplied records of individual firefighters including the number and type of incidents attended. The cohort was linked to the Australian National Death Index and Australian Cancer Database. Standardised mortality ratios and standardised cancer incidence ratios were calculated separately for paid and volunteer firefighters. Volunteer firefighters were grouped into tertiles by the duration of service and by a number of incidents attended and relative mortality ratios and relative incidence ratios calculated. Results: For volunteer firefighters (n=37 962), the overall risk of mortality and risk from all major causes of death were reduced when compared with the general population whether or not they had ever attended incidents. Volunteer firefighters had a similar cancer incidence when compared with the general population for most major cancer categories. Female volunteer firefighters have usually attended few fires. Of those who had turned out to incidents, only one-third had attended more than 12 fires about half the number for male volunteers. Mortality and cancer incidence for paid female firefighters (n=1682) were similar to the general population but the numbers were small and so power was limited. Conclusions: Female volunteer firefighters have a cancer incidence similar to the general population but a reduced risk of mortality which is likely to be a result of a 'healthy volunteer' effect. Most of the paid female firefighters were relatively recent recruits and it will be important to monitor the health of this group as more women are recruited to front-line firefighting roles.